Quantity surcharges and consumer awareness in a new retail environment - Zotos, Yorgos; Boutsouki, Christina; Palla, Polyxeni (My University, 2010)
Purpose – The purpose of this paper is to examine the evolution of the quantity surcharge phenomenon as a conscious pricing policy as well as the resulting consumer awareness and reactions to quantity surcharges. Design/methodology/approach – The approach taken is a comparative analysis of two distinct time periods involving two store audits and two consumer surveys conducted in 1989 and 2007. Findings – The findings indicate that the quantity surcharge incidents recorded in the market in both periods are the result of a conscious pricing policy. At the same time, evidence suggests that the more mature the market becomes, the less frequent and less intense the phenomenon of quantity surcharges becomes. Consumers’ attitude and reaction to quantity surcharges are also discussed indicating that the market’s evolution has also an effect on consumers. Originality/value – The paper discusses quantity surcharges as a conscious pricing policy and examines the effect of retail change on the quantity surcharge phenomenon.
Keywords: Retailing; Greece; Consumer behaviour; Pricing policy